Рецепция творчества Андрея Платонова в Воронеже: к проблеме формирования „локальных текстов” - Tamara Nikonowa (Studia Rossica Posnaniensia)
The article considers the process of studying Andrei Platonov’s literary work on his native land. The process is examined in light of today’s topic of literary criticism concerning studying “local texts” which insert the regional tradition into the national structure context.